The prevalence of dental impacts on daily performances in older people in Northern Thailand. - Srisilapanan P. (2014)
OBJECTIVE: To assess the prevalence of oral related impacts on the quality of daily life in older Thais. DESIGN: A cross-sectional study on a non-random sample. SETTING: Metropolitan area of Chiang Mai, Thailand Subjects: 707 older individuals living independently, aged 60 to 74 years, 549 were dentate, 158 were edentate. METHODS: Clinical examination and questionnaire for the Oral Impacts on Daily Performances (OIDP) index and on dental behaviours. RESULTS: About one half of the older people interviewed (52.8%) had at least one OIDP oral impact. The most common performance affected was eating (47.2%). The two main symptoms that caused oral impacts in the total sample were functional limitation and pain. The majority of older people had low OIDP scores below 8.0 (76.4%). Almost one in 10 had OIDP scores above 16.0. Individuals with a high income were more likely to have lower OIDP score (p<0.001). Subjects who had attended a dentist were more likely to have no oral impacts (p=0.02). There was a significant difference between OIDP scores related to some clinical variables; dental status (p=0.002), having mobile teeth (p=0.005), periodontal attachment loss (p<0.001), missing anterior and posterior teeth (p<0.001). CONCLUSIONS: Oral impacts that affected quality of life of older people were relatively common but not severe. The impacts were related to some social and clinical variables.